Effect of 3D earthquake on response of circular steel bridge piers and its influence on capacity prediction - Kulkarni, Nishigandha G.; Kasai, Akira (Journal of Structural Engineering, 2025)
Present work deals with investigation of coupling effect due to vertical component (UD) along with two horizontal components (EW, NS) of earthquake on the response of steel bridge piers with pipe section, for this purpose nonlinear dynamic analysis are carried out. Comparison between maximum responses due to EW-NS-UD and EW-NS earthquake motions indicated no significant change in strain and deformation values of piers but considerable amplification is observed in axial force when UD component included. Hence, to evaluate the effect of varying axial force on the capacity of the steel circular columns, static analysis are performed by applying different varying axial force patterns including bi-directional lateral loading. Although the distorted hysteretic strength-displacement curves are noticed for varying axial force cases, their energy dissipation curves coincided with those when axial force remains constant and equivalent to mean value of varying axial force cases. This indicates that, allowable strain formula based on bidirectional lateral loading and constant axial force on steel columns could be applicable in seismic design process of bridge piers when EW-NS-UD components are active.